Digital Based Sustainable Tourism Management and Local Wisdom in Serangan Village (Lembaga Contrarius Indonesia, 2026)
Bali currently possesses 238 designated tourism villages, including Serangan Village, which is classified as a pioneering tourism village (desa wisata rintisan). Several challenges persist among tourism villages in Bali, particularly those in the early stages of development; these include limited infrastructure, inadequate road access, and a lack of supporting facilities such as tourist information centers and proper sanitation. Furthermore, management and governance issues remain a critical concern. Many tourism villages in Bali still lack professional management, leading to suboptimal promotion, stagnant tourism product development, and minimal collaboration with key stakeholders, including local governments and the tourism industry. Additionally, many local residents lack the necessary skills in tourism management, digital marketing, and foreign languages. Consequently, in-depth research on sustainable tourism management integrated with digital transformation and local wisdom—is essential to ensure the long-term viability of tourism in Serangan Village.